2019
DOI: 10.1126/sciadv.aaw1644
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation reprogramming, TE derepression, and postzygotic isolation of nascent animal species

Abstract: We present evidence for the dual role of epigenetics and transposable elements have a dual role in the reproductive isolation of nascent species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 48 publications
(85 reference statements)
5
53
2
Order By: Relevance
“…47 . As work in other taxa has revealed that transposon polymorphisms contribute to adaptive evolution 48,49 and speciation 50 , future studies on pTSsa2 should investigate such possibilities in Salmo. We also showed that Atlantic salmon deletion SVs are more likely to overlap genes retained as ohnolog pairs from the Ss4R WGD event compared to singleton genes, and demonstrate SV overrepresentation in ohnolog genes according to their expression properties.…”
Section: Discussionmentioning
confidence: 99%
“…47 . As work in other taxa has revealed that transposon polymorphisms contribute to adaptive evolution 48,49 and speciation 50 , future studies on pTSsa2 should investigate such possibilities in Salmo. We also showed that Atlantic salmon deletion SVs are more likely to overlap genes retained as ohnolog pairs from the Ss4R WGD event compared to singleton genes, and demonstrate SV overrepresentation in ohnolog genes according to their expression properties.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also evidenced the effect of TEs on deleteriousness in other salmonids. In common garden environments, hybrid breakdown in Lake whitefish ( Coregonus clupeaformis ) has been associated with TE reactivation caused by a genomic shock (genomic incompatibility) and associated hypomethylation in hybrids, leading to a malformed phenotype and aneuploidy (Dion‐Côté, Renaut, Normandeau, & Bernatchez, 2014; Dion‐Côté et al, 2017; Laporte et al., 2019). Overall, this highlights the importance of increasing our understanding of the (mal)adaptive role of such structural variants compared to SNP variation, especially in small populations (Mérot, Oomen, Tigano, & Wellenreuther, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…SVs are increasingly recognized for their important role in a wide spectrum of evolutionary processes such as in environmental adaptation (Van't Hof et al, 2016;Wellenreuther, Rosenquist, Jakson, & Larson, 2017), reproductive isolation (Berdan, Blanckaert, Butlin, & Bank, 2019;Laporte et al, 2019), life cycles and development (Mérot et al, 2018;Cayuela et al, 2020) and speciation (Rieseberg, 2001; Serrato-Capuchina & Matute, 2018).…”
mentioning
confidence: 99%